2010
DOI: 10.1039/c0jm01342k
|View full text |Cite
|
Sign up to set email alerts
|

Facile synthesis of mesoporous N doped zirconium titanium mixed oxide nanomaterial with enhanced photocatalytic activity under visible light

Abstract: The present paper deals with a hydrazine mediated synthesis of high surface area and thermally stable N-doped zirconium titanium mixed oxide with enhanced photocatalytic activity towards reduction of selenium (VI) to metallic Se 0 under visible light. Materials were synthesized at pH ¼ 2 by varying the hydrazine concentration and characterized by XRD, TEM, BET method, XPS, Raman spectroscopy and UV-vis solid state spectra. Presence of low amount of zirconium oxide (10 wt%) helps in phase stabilization and main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 38 publications
0
23
0
Order By: Relevance
“…The N-mp-TiO 2 particles were used for the conversion of azoxybenzene to amines or 2-phynylindazoles with methanol using a 365 nm medium-pressure mercury lamp. In addition to introducing N and Ti 3+ , hydrazine increased the surface area from 74 to 134 m 2 /g due to hydrazine decomposition [134,172]. The yield of 4,4 -azoxyanisole by catalytic reductive cleavage on N-mp-TiO 2 (95.7%) in methanol under UV (365 nm) light illumination is higher than that on undoped mp-TiO 2 (60.3%) and P25 (50.6%).…”
Section: Hydrazinementioning
confidence: 88%
See 3 more Smart Citations
“…The N-mp-TiO 2 particles were used for the conversion of azoxybenzene to amines or 2-phynylindazoles with methanol using a 365 nm medium-pressure mercury lamp. In addition to introducing N and Ti 3+ , hydrazine increased the surface area from 74 to 134 m 2 /g due to hydrazine decomposition [134,172]. The yield of 4,4 -azoxyanisole by catalytic reductive cleavage on N-mp-TiO 2 (95.7%) in methanol under UV (365 nm) light illumination is higher than that on undoped mp-TiO 2 (60.3%) and P25 (50.6%).…”
Section: Hydrazinementioning
confidence: 88%
“…However, with hydrazine (N 2 H 4 ), titania is expected to be co-doped with both Ti 3+ and N and is therefore to synergistically absorb more visible light and potentially be a more effective redox catalyst than TiO 2 -doped with either species alone. Aman et al explored this concept using Ti 3+ and N-mp-TiO 2 nanoparticles for enhanced photocatalytic activity under visible light [134]. The Ti 3+ /N-mp-TiO 2 showed higher photocatalytic reduction of selenium to metallic Se • under visible light illumination compared to undoped TiO 2 .…”
Section: Hydrazinementioning
confidence: 99%
See 2 more Smart Citations
“…They also claimed that the doping of Zr ions in TiO 2 lattice could reach about 30%. Recent reports show that the doping of zirconium in the lattice of TiO 2 prevented the anatase to rutile phase transformation during calcination [16][17][18]. Schiller et al observed that Zr-doped TiO 2 showed a high phase stability and the anatase-type structure was maintained even after heat treatment at 800°C [18].…”
Section: Visible Light Photocatalytic Activitymentioning
confidence: 99%